Papillary carcinoma of thyroid and pregnancy - Rawal, S; Gurung, G (Journal of Institute of Medicine Nepal, 2013)
Two cases of Papillary carcinoma of thyroid and pregnancy were managed, one with the existing disease diagnosed during pregnancy and the other with a history of near total thyroidectomy. A multidisciplinary approach in the management of both the mothers lead to an uneventful pregnancy, caesarean section with good outcome and were discharged in good health. DOI: http://dx.doi.org/10.3126/joim.v34i3.8919 Journal of Institute of Medicine, December, 2012; 34:54-57